2019
DOI: 10.1093/infdis/jiz318
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Sequencing-Based Investigation of Viruses in Human Cancers by Multienrichment Approach

Abstract: Background Viruses and other infectious agents cause more than 15% of human cancer cases. High-throughput sequencing-based studies of virus-cancer associations have mainly focused on cancer transcriptome data. Methods In this study, we applied a diverse selection of presequencing enrichment methods targeting all major viral groups, to characterize the viruses present in 197 samples from 18 sample types of cancerous origin. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 49 publications
(46 reference statements)
0
32
0
Order By: Relevance
“…That was the case in the study linking febrile Kenyan adults with Kadiprio virus, which was initially considered to be the causative agent but was eventually found to be a part of QIAamp Viral RNA Mini Kit (Qiagen) kitome ( Ngoi et al, 2016 ). In a recent study, Mollerup et al (2019) used NGS to search for viruses in human cancers and found Merkel cell polyomavirus (MCPyV) in Merkel cell carcinomas. However, close similarity of all MCPyV sequences found across samples allowed studies to conclude laboratory surfaces as the source of contamination ( Foulongne et al, 2011 ; Mollerup et al, 2019 ).…”
Section: Contaminants Detected In Viral Studiesmentioning
confidence: 99%
“…That was the case in the study linking febrile Kenyan adults with Kadiprio virus, which was initially considered to be the causative agent but was eventually found to be a part of QIAamp Viral RNA Mini Kit (Qiagen) kitome ( Ngoi et al, 2016 ). In a recent study, Mollerup et al (2019) used NGS to search for viruses in human cancers and found Merkel cell polyomavirus (MCPyV) in Merkel cell carcinomas. However, close similarity of all MCPyV sequences found across samples allowed studies to conclude laboratory surfaces as the source of contamination ( Foulongne et al, 2011 ; Mollerup et al, 2019 ).…”
Section: Contaminants Detected In Viral Studiesmentioning
confidence: 99%
“…Microscopic techniques like transmission electron microscopy (TEM) have not only benefited our understanding of viral structure, but they have also aided in the support of novel virus identification from shotgunbased sequencing studies [39,40,94,95]. Perhaps the most comprehensive study characterizing viruses from a variety of sample types associated with the development of various cancers utilized a diverse selection enrichment method targeting all major viral groups followed by high-throughput sequencing [96]. This study investigated total DNA and RNA, mRNA, retroviral [97] and vertebrate viral capture [98], as well as enrichment of small circular DNA capture [99].…”
Section: Methods For Investigating the Human Viromementioning
confidence: 99%
“…Recent studies have indicated that global virome signatures may serve as markers of cancer development. Viral metagenomic signatures have been detected in lung adenocarcinoma biopsies (Cai et al, 2021) and more than 100 tumor samples, including oral, breast, colon, and genitourinary cancers (Mollerup et al, 2019). Cantalupo et al suggested that HPV, a known cause of cervical cancer and potentially other genitourinary cancers, is additionally correlated with tumor progression in head and neck cancers as well as bladder cancers (Cantalupo et al, 2018;IARC, 2009).…”
Section: Nonbacterial Cancer-associated Microbesmentioning
confidence: 99%